Student first? A case study examining the student-athlete support services at an NCAA Division I Football Bowl Subdivision (FBS) Institution - Ishaq, Farah; Stensland, Peyton; Otto, Marcella (Journal of Amateur Sport, 2023)
The purpose of this study was to examine the current student-athlete support services at an NCAA Division I FBS level institution through the lens of high impact educational practices. The researchers considered the overall college athlete experience by identifying and describing what resources student-athlete support services provide, how college athletes are (or are not) utilizing these services and applying high impact educational practices to these services. Employing a qualitative approach, 14 semi-structured interviews with college athletes and administrators presented several themes addressing the implementation of high impact educational practices. The results presented are of importance to athletics administrators interested in understanding how to develop meaningful student-athlete support services, while supporting college athlete interests and constraints. Athletics administrators can learn to establish on-campus programming for their college athletes in addition to creating a comfortable climate and connection between college athlete support services and on-campus resources.